Socio-cultural impacts of tourism in Iran : a study of Masooleh and Sare'in / Hamira Zamani-Farahani - Zamani-Farahani, Hamira (2011)
There has been unceasing interest in the study of socio-cultural impacts of tourism worldwide. The results of studies in this field are pertinent for planning and policy making purposes especially in the development of sustainable tourism. The main aim of this study was to examine the socio-cultural impacts of tourism and explore the factors that are related to host perceptions in the Islamic and developing country of Iran. This research focused on two small tourist destinations in Iran, Masooleh and Sare’in, where, tourism development is in its early stages. Drawn from empirical studies and research as well as concepts and theories, a conceptual research framework was proposed. Based on the framework several hypotheses were developed to test the relationships between the independent variables, which include Tourism Development Characteristics, Host-Tourist Interaction, Host Profiles, and Religiosity, with the dependent variable, which is the perceived Socio-Cultural Impacts of tourism by local people. A structured questionnaire back-to-back translated into the Persian language was used as the main data collection method. All the occupied houses (the first 198) from the center of the main tourist areas of the two towns were sampled. A minimum of two adults (above 18 years old) from each house were requested to answer the questionnaire. Finally, a total of 500 usable questionnaires were returned and analyzed. The results revealed that residents largely experience positive socio-cultural impacts of tourism development in their areas. They were also highly supportive of the current and the future tourism development. All the predictor variables of Tourism Development Characteristics, Host-Guest Interaction, Host Profiles, and Religiosity had significant relationships with Socio-Cultural Impacts of Tourism in the study areas. Among these predictors, Host-Tourist Interaction was found to be the most important factor in influencing the perception of socio-cultural impacts of tourism. The study contributes to the further extension of knowledge in socio-cultural impacts research when both the type and the level of Islamic religiosity have positive significant relationships with the perception of socio-cultural impacts of tourism. The socio-demographic profiles of gender, marital status, length of residency, educational achievement and employment in a tourism related job had significant relationships with the perception of the socio-cultural impacts of tourism in the areas. The results of this study support the theories of Destination Life Cycle Model (Butler, 1980), Doxey Irritation Index (Doxey, 1976) Social Exchange theory (Ap, 1992) and Social Distance theory (Thyne et al., 2006). More importantly, the study has confirmed that Islamic religiosity did not, in principle, play a role in instilling negative perceptions towards tourism development. Based on the results some pertinent theoretical, managerial and marketing implications of the study are discussed.